Chromosome-scale genome assembly of the transformation-amenable common wheat cultivar 'Fielder'. (12th July 2021) - Sato, Kazuhiro; Abe, Fumitaka; Mascher, Martin; Haberer, Georg; Gundlach, Heidrun; Spannagl, Manuel; Shirasawa, Kenta; Isobe, Sachiko
Abstract: We have established a high-quality, chromosome-level genome assembly for the hexaploid common wheat cultivar 'Fielder', an American, soft, white, pastry-type wheat released in 1974 and known for its amenability to Agrobacterium tumefaciens -mediated transformation and genome editing. Accurate, long-read sequences were obtained using PacBio circular consensus sequencing with the HiFi approach. Sequence reads from 16 SMRT cells assembled using the hifiasm assembler produced assemblies with N50 greater than 20 Mb. We used the Omni-C chromosome conformation capture technique to order contigs into chromosome-level assemblies, resulting in 21 pseudomolecules with a cumulative size of 14.7 and 0.3 Gb of unanchored contigs. Mapping of published short reads from a transgenic wheat plant with an edited seed-dormancy gene, TaQsd1, identified four positions of transgene insertion into wheat chromosomes. Detection of guide RNA sequences in pseudomolecules provided candidates for off-target mutation induction. These results demonstrate the efficiency of chromosome-scale assembly using PacBio HiFi reads and their application in wheat genome-editing studies.